Simultaneous Viral Whole-Genome Sequencing and Differential Expression Profiling in Respiratory Syncytial Virus Infection of Infants. (23rd July 2020) - Lin, Gu-Lung; Golubchik, Tanya; Drysdale, Simon; O'Connor, Daniel; Jefferies, Kimberley; Brown, Anthony; de Cesare, Mariateresa; Bonsall, David; Ansari, M Azim; Aerssens, Jeroen; Bont, Louis; Openshaw, Peter; et al.
Abstract: Targeted metagenomics using strand-specific libraries with target enrichment is a sensitive, generalized approach to pathogen sequencing and transcriptome profiling. Using this method, we recovered 13 (76%) complete human respiratory syncytial virus (RSV) genomes from 17 clinical respiratory samples, reconstructed the phylogeny of the infecting viruses, and detected differential gene expression between 2 RSV subgroups, specifically, a lower expression of the P gene and a higher expression of the M2 gene in RSV-A than in RSV-B. This methodology can help to relate viral genetics to clinical phenotype and facilitate ongoing population-level RSV surveillance and vaccine development. Clinical Trials Registration . NCT03627572 and NCT03756766.